Erectile Dysfunction is a Common Problem in Interstitial Lung Diseases - Fløe, Andreas; Hilberg, Ole; Wijsenbeek, Marlies; Bendstrup, Elisabeth (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Introduction: Erectile dysfunction (ED) is related to chronic diseases, including COPD. The pathogenesis may involve chronic hypoxia, which is common in interstitial lung disease (ILD). We aimed to study the relationship between ILD and ED. Method: Male patients with ILD detected by high-resolution computed tomography (HR-CT) and/or histopathological findings in a lung biopsy were prospectively enrolled at two European ILD centers. Participants were asked to fill in the International Index of Erectile Function questionnaire (Danish or Dutch version). Information on type of ILD, lung function tests, 6-minute walking test (6MWT), co-morbidities, medication and smoking history was obtained from patient records. Results: Of 82 enrolled patients, 54 patients (65.9%) returned the questionnaire. Mean age was 66.8 years (SD: 9.03). Twenty-six patients (48.1%) had IPF. Overall, 38 (70.4%) had some degree of ED, thirty (56.6%) had moderate to severe ED, and 23 (43.4%) had severe ED. Low diffusion capacity and high body mass index showed a trend of increasing risk of moderate to severe ED. The risk increased with age (OR per 5-year increase=2.63 (1.25; 5.53)) and decreased with 6MWT distance (OR per 50 m increase=0.60 (0.41; 0.89). Only two patients (6.7%) received specific treatment with phosphodiesterase-5 inhibitors. Conclusion: Severe ED is a common problem in men with ILD, and is associated with poor walking distance and high age. Treatment coverage is low, and physicians should address this problem as a part of the routine care.